Carta del Mayor Davison, "Porto Rico Battalion" al "Adjutant General" - Todd, Roberto H.; Davison, L. P. (My University, 1899)
Permiso pedido para contratar un oficinista
Keywords: Headquarters, Department of Porto Rico